Implan dental sebagai perawatan alternatif untukrehabilitasi kehilangansebuah gigi Dental implant as an alternative treatment for single tooth loss rehabilitation - Vincentius Harsono; Harly Prabowo (DiscoverSys Inc., 2012)
Although only one, tooth loss, can cause a wide range of problems. They are difficulty of chewing, shifting teeth, andaesthetics problems. There are two categories of dentures, namely removable and fixed dentures. Lately, the paradigmof tooth loss rehabilitation has changed. Removable denture has been used in a long period, but this alternativetreatment has several disadvantages. Fixed denture is preferred especially for a single tooth loss because of thecomfort and resemblance to natural teeth. Currently, implant supported fixed denture is an option in replacing thefixed denture. Its advantages are no teeth reduction needed and ultimate emerging profile. In these three cases,reported comfort of using dental implants, especially in the case of single tooth loss. At control stage, the function ofmastication and aesthetic factors was also uncomplaint.